Evaluación del sistema de control interno en el área de créditos y riesgos en una institución microfinanciera y su incidencia en la gestión. Caso: Micredito S.A.C. en el departamento de La Libertad, periodo 2010-2011 - Valderrama Isla, César Antonio (2012)
The good performance of the Peruvian economy in recent years has been conducive to the emergence of microfinance institutions across the country, with greater presence in the departments of the North and Central (Peru is the country with the best conditions for microfinance in Latin America and the Caribbean-2010 microscope developed by the Economist Intelligence Unit / IDB). This is the case of La Libertad region who has grown exponentially in recent years, largely helped by microcredits granted to certain segments of the economically active population (EAP). However, many microfinance institutions have heavy bags (delinquent) that are in some cases 30% or 40% of your portfolio, be a serious problem in the medium and long term. The loans made without regard to the regular procedures of credit, poor internal control, dishonesty and lack of values of some officials are the main causes of this rate. This study analyzed the Internal Control System in a microfinance institution. Evaluating processes and procedures in granting credits, develop research specifically in the area of Credit and Risk of a microfinance institution that is not regulated by the SBS, but tries to follow the guidelines given by it to effect control. Creating controls is one of the most efficient ways to ensure optimal compliance objectives in order to prevent fraud. Conducted the study it was found that the company has a Credit Policy Manual which is the maximum guide every analyst and administrator must apply at the time of credit loans. However, this Policy and Procedure Manual Credit does not apply in the way it should. An analysis of those procedures could be determined failures of implementation of the manual, allowing them individually and to propose possible solutions to address them Having an internal control system efficiently and effectively is important for the successful management of the company. Given that in this way improve the options for meeting the goals and objectives of expansion and positioning of the institution, having a cattle market and loyal customers. The data of this investigation refer to the Company MICREDITO SAC. and their operations in the department of Liberty in 2010 and the first half of 2011.